Fang-Ji-Huang-Qi-Tang Attenuates Degeneration of Early-Stage KOA Mice Related to Promoting Joint Lymphatic Drainage Function. (20th March 2020) - Han, Haihui; Ma, Yinghui; Wang, Xiaoyun; Yun, Ruisheng; Lu, Sheng; Xia, Mengxiong; Wang, Yongjun; Shi, Qi; Zhai, Weitao; Liang, Qianqian; Xu, Hao
Abstract : Osteoarthritis (OA) is a chronic degenerative joint disease characterized by the breakdown of articular cartilage, subchondral bone remodeling, and inflammation of the synovium. In this study, we investigated whether Fang-Ji-Huang-Qi-Tang (FJHQT) decoction improved the joint structure of OA or delayed the process of knee joint degeneration in OA mice by promoting lymphatic drain function. The mice were randomly divided into four groups, the sham group, the PBS group, the FJHQT-treated group, and the Mobic-treated group. The mice in each group were tested for lymphatic draining function at 4, 6, 8, and 10 weeks postsurgery (WPS), then sacrificed ( N  = 10/group). Using a near-infrared indocyanine green (NIR-ICG) lymphatic imaging system, we found that the lymphatic drain function was significantly reduced in the PBS group compared with the sham group. After treatment with the FJHQT decoction, the lymphatic draining function improved at 4 wps and 6 wps. The results of the analysis indicated a strong correlation between lymphatic draining function (ICG clearance) and the degree of joint structural damage (OARSI score). By Alcian blue/orange G (ABOG) staining of the paraffin sections, the FJHQT-treated group exhibited less cartilage destruction and lower OARSI scores. Moreover, the result of immunohistochemical staining (IHC) shows that FJHQT decoction increased the content of type II collagen in knee joints of OA mice at 4 wps and 6 wps. By the double immunofluorescence staining of podoplanin and smooth muscle actin in the paraffin sections, the capillaries and mature lymphatics in the FJHQT group increased at 4 wps. In conclusion, the FJHQT decoction can increase lymphatic vessel number, promote joint lymphatic draining function, and postpone knee osteoarthritis pathologic progression in the early stage of a collagen-induced mouse model. Therefore, the application of sufficient lymphatic drainage in the knee joint may be a new treatment method for knee joint osteoarthritis (KOA).